Critical Immersive-Triggered Literacy as a Key Component for Inclusive Digital Education - Chrysoula Lazou; Avgoustos Tsinakos (MDPI AG, 2023)
The present empirical study investigates, analyzes, and discusses the affordances and limitations of an augmented reality (AR)-based educational intervention for the critical digital awareness of secondary school students through a sociocultural framework of instruction. The design of the educational intervention focuses on the empowerment of students' critical digital skills in the new media produsage ecosystem in parallel with the development of target language skills through content and language integrated learning (CLIL) in a mobile augmented reality (MAR)-based transnational educational setting. This study focuses on examining the usefulness rather than the digital use of MAR from a socio-constructivism perspective with 77 participants from diverse socio-cultural backgrounds and educational settings. More specifically, an investigation of the potential of internalization of new knowledge through immersive-triggered inclusive educational practices is carried out, examining the effectiveness of the universal design for learning principles (UDL) as a pedagogical framework for AR-based instruction related to long-term memory retention, the synthesis of meaningful learning instances, and the creation of new knowledge. The study findings suggest that AR-based instruction, if incorporated into a robust pedagogical framework, can enhance attention and long-term memory retention, provide meaningful, inclusive learning opportunities, and facilitate digital well-being in the ever-evolving complex learning ecosystem. This study concludes by proposing the term of critical immersive-triggered literacy (CIT Literacy), defined as a skill development framework that triggers learners' attention and facilitates digital well-being for meaningful learning instances via immersive technologies.